Dietary Bacitracin Methylene Disalicylate Improves Growth Performance by Mediating the Gut Microbiota in Broilers - Jingshang Li; Yingping Xiao; Qian Fan; Hua Yang; Caimei Yang; Guolong Zhang; Shengchang Chen (MDPI AG, 2022)
The growth performance of livestock and poultry has always been a concern. However, much work is currently focused on the selection of breeds and diets to improve the growth performance of livestock and poultry. Furthermore, numerous studies have shown that the gut microbiota is closely related to the growth performance of livestock and poultry. At present, there are many reports on the impact of antibiotic intervention on the structure of gut microbiota. However, there are few reports on the influence of antibiotic intervention on the structure of intestinal microbes and the effect of this change on growth performance. Bacitracin methylene disalicylate (BMD) intervention changes the microbial structure in the caecum of broilers at different growth stages, as shown in this study. To further reveal the potential relationship between gut microbiota changes and growth performance caused by BMD intervention, correlation analysis was used for analysis. A total of 144 1-day-old male Cobb-Vantress were randomly divided into two groups. In addition to antibiotic-free starter mash diets, starter mash diets supplemented with 55 mg/kg BMD were also used, called the CON group and the BMD group, and lasted 28 days. (1) These study results showed that adding BMD to the diet had a significant effect on the growth performance of broilers. Compared with the CON group, the body weight of the BMD group increased significantly by 11.08% and 20.13% on Days 14 and 28, respectively (p < 0.05). Similarly, at 0-14, 14-28 and 0-28 days of age, the average daily gain of the BMD group increased significantly by 12.28%, 24.49% and 20.80%, respectively. The average daily feed intake of the BMD group increased significantly by 18.28%, 27.39% and 24.97% (p < 0.05). In addition, at 0-28 days of age, the feed conversion ratio increased significantly by 5.5% (p < 0.05). (2) Alpha diversity results show that BMD intervention has an impact on gut microbiota at different growth stages. (3) The early intervention significantly affected 7 taxa by Day 14, followed by 22 taxa by Day 28, which is similar to the results in the caecal flora. Compared with the CON group, the Christensenellaceae R-7 group had the highest linear discriminant analysis (LDA) score on Day 28. In addition, Pearson's correlation analysis showed that the Lachnospiraceae FCS020 group was significantly negatively correlated with growth performance. In general, these results indicate that dietary supplementation of BMD has an effect on broiler gut microbiota structure and growth performance. However, changes in growth performance may be caused by the gut microbiota structure.